2009
DOI: 10.1007/s00422-009-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

Washout filter aided mean field feedback desynchronization in an ensemble of globally coupled neural oscillators

Abstract: We propose an approach for desynchronization in an ensemble of globally coupled neural oscillators. The impact of washout filter aided mean field feedback on population synchronization process is investigated. By blocking the Hopf bifurcation of the mean field, the controller desynchronizes the ensemble. The technique is generally demand-controlled. It is robust and can be easily implemented practically. We suggest it for effective deep brain stimulation in neurological diseases characterized by pathological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In normal brain function, synchronization within and between neural populations is an important mechanism for neural signaling and information processing (Hauptmann et al 2005;Luo et al 2009). In recent years, synchronization has been extensively studied in different contexts by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In normal brain function, synchronization within and between neural populations is an important mechanism for neural signaling and information processing (Hauptmann et al 2005;Luo et al 2009). In recent years, synchronization has been extensively studied in different contexts by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies rely on phase models. The mean-field feedback is applied using a particular resonant filter (Tukhlina et al, 2007; Luo et al, 2009) or a purely proportional feedback (without derivative terms) is analyzed with a finite-dimensional model, using an approach based on Lyapunov functions (Franci et al, 2011, 2012). The model of Rubin and Terman is exploited in Leondopulos (2007), Liu et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other models and feedback schemes similar to (3)-(4) have been considered in the literature for the study of desynchronization via mean-field feedback [22][23][24]35,[41][42][43][44][48][49][50], achieving encouraging results that support this control strategy. Apart from computational studies [22][23][24], several analytical results have been derived.…”
Section: Comparison With Existing Approachesmentioning
confidence: 77%
“…Motivated by the same medical problem, different works have appeared about the physics of a population of interconnected oscillators under the effect of a mean-field feedback [22,23,35,[42][43][44]49,50], mostly relying on numerical analysis. On the one hand, these studies have shown that mean-field feedback DBS is a promising strategy for desynchronizing pathological neuronal populations.…”
mentioning
confidence: 99%